Sexual assault: a descriptive study of 2500 female victims over a 10‐year period. (15th October 2014) - Larsen, M‐L; Hilden, M; Lidegaard, Ø
<x xml:space="preserve">Abstract</x> Objective To describe the victims of sexual assault and the circumstances in which the assaults occur. Design Descriptive case study. Setting Centre for Victims of Sexual Assault (CVSA), Rigshospitalet, Copenhagen, Denmark. Population or sample A total of 2541 women attending CVSA from 2001 to 2010. Methods All women attending CVSA underwent a standardised data collection procedure. Descriptive bivariate analysis and logistic regression analysis were performed. Main outcome measures Associations between different assault characteristics and (1) the age of the victim and (2) the relationship between victim and perpetrator. Results Two‐thirds of the victims were aged 15–24 years. Seventy‐five percent had met the perpetrator before the sexual assault and 70% reported the assault to the police. A physical injury was found in 53, and 27% sustained an anogenital lesion. Alcohol was involved in 60% of the cases. One‐third of the victims had experienced a previous sexual assault(s). Women were more likely to report to the police when they were assaulted by a stranger (odds ratio [OR] 1.9, 95% confidence interval [95% CI] 1.3–2.6) and sustained a physical injury (OR 1.7, 95% CI 1.4–2.2) or anogenital lesion (OR 1.5, 95% CI 1.1–2.0). Women aged 45 years or older were more likely to sustain a physical injury (OR 2.0, 95% CI 1.2–3.2) or an anogenital lesion (OR 2.1, 95% CI 1.4–3.2). Conclusions Our results challenge the typical stereotype of a violent rape attack by a stranger, which is important in creating an environment where women are not reluctant to seek help after a sexual assault. Young age and drinking alcohol were risk factors for sexual assault, and we need to address this when considering preventive strategies.